THE INTERACTIVE ROLE OF SERVANT LEADERSHIP IN THE RELATIONSHIP BETWEEN ORGANIZATIONAL AGILITY AND ORGANIZATIONAL EXCELLENCE (AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES AT AL-AIN PRIVATE UNIVERSITY IN THI QAR) (World Economics and Finance Bulletin, 2025)
The study aims to know the interactive role of servant leadership and to know the relationship between organizational agility and organizational excellence through application in one of the Iraqi private universities and through that to know the impact of servant leadership on organizational excellence in Al Ain University, the organization under study, where (organizational agility) was adopted as an independent variable and the interactive variable represented by (servant leadership) was adopted and (organizational excellence) was adopted as a dependent variable and the problem of the study was represented by the question that stated (Is there an interactive role for servant leadership in the relationship between organizational agility and organizational excellence in the university under study), while the study sample was represented by all employees at Al Ain University and in order to determine the relationship between the variables, a set of primary and sub-hypotheses were developed and the questionnaire form was designed as a primary tool for collecting data and information based on ready-made measures to discover the relationships of influence and correlation between the study variables. The study community was used, which numbered (1424) and based on the table designed by Morcan, which shows the appropriate sample size for each community, ((302 were distributed, of which (260) were retrieved, i.e. (22 were non-refundable, and (20) were not valid for analysis, to be the total number
Keywords: Organizational Agility; Servant Leadership; Organizational Excellence